A qualitative description of barriers to visual rehabilitation experienced by stroke survivors with visual impairment in Alberta, Canada - Kiran Pohar Manhas; Katelyn Brehon; Jennis Jiang; Karim F. Damji; Fiona Costello (BMC, 2023)
Abstract Background Post-stroke visual impairment (VI) is a common but under-recognized care challenge. Common manifestations of post-stroke VI include: diplopia, homonymous hemianopia, oscillopsia secondary to nystagmus, and visual inattention or neglect. In acute care settings, post-stroke VI recognition and treatment are often sub-optimal as emphasis is placed on survival. Stroke survivors with VI often face inconsistencies when accessing care out of hospital because variable availability and subsidization of visual rehabilitation. We sought to identify gaps in care experienced by stroke survivors with VI from stroke survivors' and care providers' perspectives. Methods We conducted a qualitative description study across 12 care sites in Alberta, Canada, using semi-structured interviews. Survivor interviews focused on the health system experience. Provider interviews discussed approaches to care, perceived gaps, and current resources. Interviews were audio-recorded and transcribed. Iterative content analysis was completed using NVivo 12. We promoted rigour through an audit trail, open-ended questions, thick description, and collaborative coding. Results We completed 50 interviews: 19 survivor interviews and 31 provider interviews. The majority of survivors were male (n = 14) and recruited from community settings (n = 16). Providers varied in profession and location within the care continuum. Two key themes emerged from the provider and survivor interviews pertaining to (a) facets of visual rehabilitation (sub-themes: access, resources, and multidisciplinary professional interaction); and (b) functioning with post-stroke VI (sub-themes: early experiences post-stroke and living with VI in the real world). Conclusions The visual rehabilitation model needs to be optimized to ensure transparent inter-disciplinary communication and efficient referral pathways. Future research will focus on evaluating the effectiveness of post-stroke care from multiple perspectives in Alberta.